Voltage Regulation Of Dc Link For Microgrid Stability And Operation - Nur’ain Syakirah, Kasmat Aidi (2022)
Equal power-rating at different power set points in an isolated or grid-connected mode may result in inter-unit circulating power due to a significant mismatch between power generation and demand during network contingencies. This mismatch can occur when there is a substantial imbalance between power generation and demand (faults on the heavy load side of unintentional islanding). Because of this circulating power, the dc-link voltage limit might be exceeded, which would set off the protection mechanism and make the microgrid less reliable. When circulating power is present, the article suggests using a regulator to keep the voltage on the converter dc-link under control. It comprises a discharge resistor with a switch placed across the dc-link capacitor. This switch is actuated by a control algorithm when the voltage across the dc-link exceeds an established limit. The case studies of dc-link connected in parallel input energy sources is investigated. In addition, a realistic microgrid is built and put through its paces as a low-voltage (LV) network test to confirm the concept and the regulatory actions described. The findings of the simulation provide evidence that the suggested regulator is successful even in the presence of unforeseen network conditions.